The Senduduk fruit extract ( melastoma malabathricum L ) as a colonization invitation pasta in the establishment of plaque - Listrianah Listrianah; Marlindayanti Marlindayanti; Yufen Widodo (OMNICODE Journal (Omnicompetence Community Developement Journal), 2022)
This community service activity is to improve the dental health of the community in the Air Batu area, Talang Kelapa District, Banyuasin Regency Palembang , by utilizing the senduduk fruits (melastoma malabatricum) which grows wild around his residence. By having good oral and dental health, especially children, it is hoped that the growth and development of children in the Air Batu area, Talang Kelapa District, Banyuasin Regency Palembang will experience growth and development according to their age. This will build a strong foundation for future generations. Community service carried out is the Community Partnership Program . Achievement target is to increase the degree of dental and oral health in the Air Batu community, Talang Kelapa District, Banyuasin Regency in 2021. The result of this activity is 50 people have been given knowledge about how to maintain oral and dental health through counseling and practiced to make senduduk fruits gel as an ingredient for measuring and detecting dental and oral hygiene. They participated in this activity from the initial stage to the mentoring, they really felt the positive impact of this community service activity, so that their dental and oral health status became better than before.